Kolak Ayam Sebagai Tradisi Kuliner Bersejarah Di Desa Gumeno, Gresik: Makna Moral, Sosial, Dan Religiusitas - Shafitry, Ikka Sharani; Octaviani, Gita Ayu Dwi; Nuraini, Fariha Sindi; Maulidiya, Gita (Program Studi Pendidikan Sejarah - Universitas Samudra, 2024)
This research examines the culinary tradition of chicken compote in Gumeno Village, Gresik Regency, which is held every 23 Ramadhan. This tradition originates from the history of Sunan Dalem and has been going on for almost 490 years. This research examines the culinary tradition of chicken compote in Gumeno Village, Gresik Regency, which is held every 23 Ramadhan. The method used in this research is a qualitative approach with semi-structured interviews, involving informants who have knowledge of local culinary delights. The research results show that chicken compote is not just a dish, but also has deep moral, social and religious meaning. This tradition functions as a community link, strengthens Gresik's cultural identity, and preserves the values ​​of togetherness and gratitude among the community. Thus, chicken compote is an important representation of culinary heritage that needs to be preserved. The method used in this research is a qualitative approach with semi-structured interviews, involving informants who have knowledge of local culinary delights. The research results show that chicken compote is not just a dish, but also has deep moral, social and religious meaning. This tradition functions as a community link, strengthens Gresik's cultural identity, and preserves the values ​​of togetherness and gratitude among the community. Thus, chicken compote is an important representation of culinary heritage that needs to be preserved